2017
DOI: 10.1088/1361-6528/aa78bc
|View full text |Cite
|
Sign up to set email alerts
|

Flexible electrochemical biosensors based on graphene nanowalls for the real-time measurement of lactate

Abstract: We demonstrate a flexible biosensor for lactate detection based on l-lactate oxidase immobilized by chitosan film cross-linked with glutaraldehyde on the surface of a graphene nanowall (GNW) electrode. The oxygen-plasma technique was developed to enhance the wettability of the GNWs, and the strength of the sensor's oxidation response depended on the concentration of lactate. First, in order to eliminate interference from other substances, biosensors were primarily tested in deionized water and displayed good e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 33 publications
0
27
0
Order By: Relevance
“…And it's Young's modulus is ≈ 3.7 MPa [38], making the stretch and strain more than 200%. Given its excellent stretch, extensibility, thermoelectric properties [39][40][41], high chemical stability, and easy use make PDMS more abundant in applications such as electronic skin [42]. Polyimide (PI) material with properties similar to PDMS (shown in Table 1), PI exhibit a poor thermal conductivity in the order of 0.1 W m −1 K −1 [43][44][45], with electrical insulating resistivity 1.5 × 10 17 cm −1 [46].…”
Section: Flexible Substratesmentioning
confidence: 99%
“…And it's Young's modulus is ≈ 3.7 MPa [38], making the stretch and strain more than 200%. Given its excellent stretch, extensibility, thermoelectric properties [39][40][41], high chemical stability, and easy use make PDMS more abundant in applications such as electronic skin [42]. Polyimide (PI) material with properties similar to PDMS (shown in Table 1), PI exhibit a poor thermal conductivity in the order of 0.1 W m −1 K −1 [43][44][45], with electrical insulating resistivity 1.5 × 10 17 cm −1 [46].…”
Section: Flexible Substratesmentioning
confidence: 99%
“…Formation of different oxygen-containing functional groups after oxygen plasma post-treatment enhances the capability of CNWs to interact with electrolyte rapidly, which further increases the specific capacitance of the material. Chen et al also reported the effect of oxygen plasma post-treatment in enhancing the reaction of CNWs with enzymes for electrochemical sensors to detect lactate enzyme [ 138 ]. Gokus et al and Wang et al explained the effect of oxygen plasma treatment on graphene to modify the photoluminescent (PL) properties [ 120 , 139 ].…”
Section: Plasma Assisted Surface Modification and Dopingmentioning
confidence: 99%
“…Chen et al reported the implementation of PECVD grown graphene nano walls (GNWs) in the fabrication of flexible electromechanical biosensor for real-time measurement of lactate [244]. In the method, crosslinking was adopted to functionalize the obtained GNWs with chitosanglutaraldehyde to immobilize lactate enzyme on GNWs using PET as the flexible substrate.…”
Section: Biosensors and Flexible Wearable Devicesmentioning
confidence: 99%